Bioethics and Christian-Catholic Religion: Two complementary rationalities - León Correa, Francisco Javier (Acta Bioethica, 2010)
After a first moment of confrontation, in the last years several authors are coming to the conviction that a fruitfuldialogue is necessary between bioethics and religion. On one hand, Catholic thinkers have reflected on the relations betweenscience and religion and faith and reason. On the other hand, secular thinkers have expressed interest in discovering theoptimal moral theology contribution to bioethical debate, in order to generate a constructive dialogue over ethical aspectsof health care and the care of human life in the biomedical field.After examining different positions, this article emphasizes constructive dialogue and the probable contribution to bioethicsof Christian theology and philosophy.